2023
DOI: 10.14202/vetworld.2023.1421-1428
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic activity of Carica pubescens aqueous seed extract and its effects on rumen fermentation and methane reduction in Indonesian thin-tailed sheep: An in vitro study

Abstract: Background and Aim: Seeds from Carica pubescens were observed to be abundant as waste. This waste contains active plant compounds whose utilization has not been studied in the livestock sector. This study was conducted to evaluate the potential of an aqueous seed extract of Carica pubescens (ASE) as an anthelmintic agent during rumen fermentation and methane reduction. Materials and Methods: Aqueous seed extract of Carica pubescens was prepared from C. pubescens cultivated in Wonosobo, Indonesia. Phytochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The industrial waste is potentially valuable for multiple uses in the ruminant industry. The in vitro research proposes it as a potential alternative to control gastrointestinal helminth infections, decrease methane emissions, and safeguard proteins [ 5 , 7 , 8 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The industrial waste is potentially valuable for multiple uses in the ruminant industry. The in vitro research proposes it as a potential alternative to control gastrointestinal helminth infections, decrease methane emissions, and safeguard proteins [ 5 , 7 , 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to SEM findings, P. falcataria bark waste harbors plant compounds essential for helminth death through damage to the helminth cuticle. Baihaqi et al [8] demonstrated through an in vitro study that Carica pubescens seed waste damages H. contortus cuticle structure, thus eliminating it. This study found that Carica seeds did not impact ruminal fermentation while lowering methane gas production, supporting earlier findings by Baihaqi et al [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations on C. pubescens seeds proved qualitatively positive, while the total phenol was 9.5 (mg GAE/g dw), flavonoids content 3,1 (mg RE/g dw) and 5.4 % total tannins. The use of active plant compounds from agoindustrial waste can be used as an alternative to worm infection control, methane reduction and protein protection winth in vitro study as done by Baihaqi on plant waste Paraserianthes falcatria bark [7], fruit peel of Carica pubescens [17] and seed of Carica pubescens [8].…”
Section: Qualitative and Quatitative Phytochemical Analysesmentioning
confidence: 99%
“…Recent in vitro research by Baihaqi et al [8] added that in vitro studies indicated that the seeds of C. pubescens inhibit H. contortus, leading to a damaged cuticle structure. The seeds of C. pubescens do not interfere with rumen fermentation characteristics but have a significant effect on methane reduction.…”
Section: Introductionmentioning
confidence: 99%